Knowledge, Attitude and Practice Regarding Pertussis among a Public University Students in Malaysia - Nur Amalina Binti Abdul Basir; Nor Azlina A. Rahman; Mainul Haque (Association of Support to Oral Health Research (APESB), 2022)
Objective: To study the knowledge, attitude, and practice (KAP) regarding pertussis among students in a public university in Malaysia. Material and Methods: This study was a cross-sectional study using convenience sampling to recruit 171 respondents. The data was collected using a self-administered questionnaire comprised of four different parts: the socio-demographic data, the knowledge, the attitude and the practice towards the prevention of pertussis. The data were analyzed using correlation, independent t- test, and ANOVA  according to the different study objectives and types of data. Results: More than half of the respondents (67.8%) indicated that they had heard about pertussis. The school or university (59.6%) was the most common source of information, followed by Internet (46.2%). The most of the respondents (43.9%) possessed moderate knowledge regarding pertussis and knew that Bordetella pertussis is the causative agent of pertussis (76.0%). A significant positive correlation between knowledge regarding pertussis with age (p=0.023) was observed, however, there was no association between age with attitude and practice (p=0.272 and 0.131, respectively). Gender and marital status did not influence the KAP regarding pertussis; nevertheless, significantly different between different faculties. Conclusion: Students from the Faculty of Medicine had the highest knowledge scores, while the students from the Faculty of Nursing had the most top attitude and practice scores compared to students from another faculty. The students from the public university generally had a good level of KAP regarding pertussis.